2004
DOI: 10.1203/01.pdr.0000100904.17064.47
|View full text |Cite
|
Sign up to set email alerts
|

Nimesulide, a Cyclooxygenase-2 Preferential Inhibitor, Impairs Renal Function in the Newborn Rabbit

Abstract: Tocolysis with nonsteroidal anti-inflammatory drugs (NSAIDs) has been widely accepted for several years. Recently, the use of the cyclooxygenase-2 (COX2) preferential NSAID nimesulide has been proposed. However, data reporting neonatal acute renal failure or irreversible end-stage renal failure after maternal ingestion of nimesulide question the safety of this drug for the fetus and the neonate. Therefore, this study was designed to define the renal effects of nimesulide in newborn rabbits. Experiments were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 52 publications
(60 reference statements)
1
14
0
Order By: Relevance
“…The RVR was significantly increased by a maximum of 92%, resulting in a significant time-dependent decrease in GFR, RBF and diuresis. We reported in the normoxemic newborn rabbit that infusion of saline solution had no significant effect on MAP and renal function over time, demonstrating the stability of the model [29]. Therefore, the further deterioration of hemodynamics and renal function observed here can be considered as a specific effect of hypoxemia.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…The RVR was significantly increased by a maximum of 92%, resulting in a significant time-dependent decrease in GFR, RBF and diuresis. We reported in the normoxemic newborn rabbit that infusion of saline solution had no significant effect on MAP and renal function over time, demonstrating the stability of the model [29]. Therefore, the further deterioration of hemodynamics and renal function observed here can be considered as a specific effect of hypoxemia.…”
Section: Discussionsupporting
confidence: 51%
“…We also previously demonstrated in the same model that the newborn's kidney is highly sensitive to cyclooxygenase 2 (COX2) inhibition and that PGs play a key role in the regulation of neonatal GFR [29], through a rapid increase of COX2 renal expression during the first two postnatal weeks [38,39]. Prostaglandin synthesis inhibition with indomethacin completely blocked the IGF-1-induced increase in GFR in vitro and in vivo [24,40,41].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Van Steenbergen et al (1998) stated that immunological and metabolic idiosyncratic reactions may be the pathogenic mechanisms of nimesulide-induced liver disease in humans. Renal adverse effects to these drugs are due to the inhibition of prostaglandin synthesis, an increase in renal vascular resistance with a concomitant decrease in diuresis, GFR, and renal blood flow acute reversible renal failure (Apostolou et al, 1997;Balasubramaniam, 2000;Prevot et al, 2004). Merlani et al (2001) has reported that the primary manifestation of nimesulide toxicity is jaundice.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, RVR increased in the indomethacin group and decreased in the OBE002 and vehicle group (Table S3); single animals in the OBE002 group had outliers in RVR which lead to discordant mean and median percentage differences (Table S3) and marked SEM values (Table S2). (Prévot et al, 2004).…”
Section: Effects Of Obe002 and Indomethacin On Renal Function In The mentioning
confidence: 99%